Robotic-assisted tracheal, carinal, and bronchial sleeve resections without lung resection: a narrative review of techniques, airway management, and early outcomes - Saavedra-Gonzalez, Karen Y.; Tapias, Luis F. (Video-Assisted Thoracic Surgery, 2026)
Background and Objective: Airway surgery remains one of the most technically challenging procedures for both surgeons and anesthesiologists. While open surgery and video-assisted thoracic surgery have historically been used, each approach carries inherent trade-offs when applied to complex airway reconstruction. The advent of robotic-assisted thoracic surgery has expanded the technical possibilities for complex airway procedures. The objective of this narrative review is to summarize the principles of tracheobronchial surgery and how they have been applied to robotic-assisted resections with lung preservation, while appraising the published preliminary experience with particular attention to anesthetic strategies, surgical techniques, and early reported outcomes.Methods: A structured literature search was conducted in July 2025 using PubMed and Google Scholar for studies published from 2015 to 2025 in English or Spanish. Eligible publications included articles describing robotic-assisted tracheal, carinal or bronchial resections with lung preservation, focusing on surgical technique and anesthetic or airway management.Key Content and Findings: The literature search initially yielded 318 records; however, only 18 cases met the inclusion criteria, representing a small evidence base predominantly composed of case reports and small series from experienced centers. Robotic-assisted resections of the central airways are an emerging approach, with limited published experience to date. Benign and malignant airway tumors were the only reported indications. Reported locations included the trachea (6, 33%), left mainstem bronchus (4, 22%), right bronchus intermedius (3, 17%), carina (3, 17%), right mainstem bronchus (1, 6%), and left LC2 minor carina (1, 6%). Anesthetic management varied and included standard selective endotracheal intubation (8, 44%), spontaneous ventilation (6, 33%), cross-field ventilation (3, 17%), and extracorporeal membrane oxygenation (1, 6%).Conclusions: In highly selected patients treated at expert centers, robotic-assisted airway resections with lung preservation appear technically feasible with encouraging early outcomes. However, current evidence is largely derived from case reports and small series with short clinical follow-up, which limits the ability to draw definitive conclusions regarding the relative safety or efficacy of this approach compared with established techniques. Further multicenter experience with longer follow-up is needed to evaluate perioperative and oncologic outcomes in complex airway surgery.